Quark masses without Yukawa hierarchies (2005)
ABSTRACT: A model based on the local gauge group SU(3)c⊗SU(3)L⊗U(1)X without particles with exotic electric charges is shown to be able to provide the quark mass spectrum and their mixing, by means of universal see-saw mechanisms, avoiding a hierarchy in the Yukawa coupling constants.